Anthropometric Measurements Analysis For Sex Determination In Human Ribs A Systematic Review - Nurul Hannim Zaidun; Aspalilah Alias; Eric Chung; Ng Wei Lin; Rani Sakaran; Nur Damia Iwani Zulkiflee; Viskasari Pintoko Kalanjati; Srinivasa Rao Sirasanagandla; Jaafar Aliyu; Choy Ker Woon (Mal J Med Health Science, 2024)
Indexed by MyCite